PENGARUH BEBAN KERJA, WORK FAMILY CONFLICT DAN REWARD TERHADAP KEPUASAN KERJA KARYAWAN - Ardina Fajar Nur Hidayah; Hengky Widhiandono; Purnadi Purnadi; Erna Handayani (Universitas Bina Taruna Gorontalo, 2024)
The study aims to test and analyze the impact of workload, work-family conflict, and rewarding on employee job satisfaction at Laksana New Swalayan Majenang. This type of research is quantitative-survey research. The sample consisted of 95 employees or a total of employees at the New Swalayan Majenang. Sampling techniques In this study using saturated sampling technique and analytical tools using SmartPLS version 3.0. The results of the study found that the workload variables were most influential with relatively large path coefficients (positive), as well as high T Statistics and significant P Values on job satisfaction, work family conflict had a negative and significant impact on job content, reward has no effect on job satisfaction.